Diagnostic value of Tc-99m-MIBI SPECT/CT in parathyroid carcinoma with lung metastasis: a case report and literature review - Zhu, Yirong; Wang, Lian; You, Jiaxi; Deng, Shengming; Shi, Yizhen; Liu, Zengli; Hong, Zhihui (Frontiers in Oncology, 2024)
PurposeParathyroid carcinoma (PC) is an extremely rare disease, typically presenting with marked elevations of serum calcium concentrations and associated with significantly increased parathyroid hormone (PTH) levels. Although it progresses slowly, approximately25% of PC patients have lung metastases. In the present study, we aimed to evaluate the role of technetium-99m methoxy isobutyl isonitrile (Tc-99m-MIBI; sestamibi) SPECT/CT scintigraphy in the preoperative localization of parathyroid adenomas, incidental metastases findings of PC, and ectopic parathyroid tissue.MethodsWe presented a rare case alongside a review of the relevant literature.ResultsWe described an unusual case of a 25-year-old female patient with co-occurrence of PC and lung metastasis. The primary PC lesion showed no radioactive uptake, while the lung metastasis presented as a hyperfunctioning nodule, successfully localized using Tc-99m-MIBI SPECT/CT and confirmed through surgical and pathological examination.ConclusionsThis case emphasized the uniqueness of Tc-99m-MIBI SPECT/CT imaging in diagnosing PC and metastatic lesions. The appropriate application of this technique may help avert the aggressive clinical progression of PC.